Occupational burnout in a sample of geriatric social care professionals in Malaysia - Rathakrishnan, R. Balan; Swami, Viren; Parasuraman, Balakrishnan; Abdullah, Muhammad Madi; Muniapan, Balakrishnan (2008)
This study examined the relationship between occupational burnout and various socio-demographic variables, workload and job clarity in a sample of geriatric social care workers in Malaysia. Maslach’s Burnout Inventory was used to categorise occupational burnout into three categories: state of emotional exhaustion, depersonalisation and reduced personal accomplishment.The results showed significant gender and marital status differences in depersonalisation. In addition, the results showed that participants with poor job clarity and those who perceived they had a heavy workload were more emotionally exhausted. These results are discussed in terms of the job stresses faced by welfare workers in Malaysia.